Ibn Khaldun's insight: Intellectual capital for entrepreneurship using wordclouds and netnography - Dicky Wahyudi (Center for Islamic Economics and Development Studies [P3EI], 2022)
Purpose – This paper aims to identify Ibn Khaldun's philosophy on the contribution of intellectual capital to increasing business performance for MSMEs.Methodology – Using literature studies and observations of online data, this paper focuses on identifying the typology of content used by internet users on Youtube channels to capture the involvement of entrepreneurs during the Covid-19 pandemic era. This study is conducted using the Netnographic method, whereas the Wordcloud technique was used to generate information for entrepreneurship from the youtube channel. The relevant channel is entitled “UMKM: Paling Tangguh Meskipun Kalah “Seksi,